The Level of Corporate Social Responsibility Disclosure of the Banks Listed in DSE of Bangladesh: A Comparative Study between Pre-Covid Period and Pandemic Period - Jahan, Kawsar; Akter, Soniya (Business and Economic Research, 2022)
<span style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">The aim of the study is to measure the extent of the Corporate Social Responsibility Disclosure (CSRD) revealing practices of the listed banks in Bangladesh and investigate the potential impacts of pandemic period and bank specific attributes on CSR disclosures on the basis of the contemporary data from 2015-2020. The study is directed with content analysis of 30 listed banks in Bangladesh during the period of 2015-2020 generating 180 sample year observations to break down the components that influence the CSR reporting of the listed banks. The study finds that CSR disclosure index decreases at 71% in 2020 and it is clearly stated that pandemic poses a significant impact on CSR reporting. This study also indicates firm age, leverage, independent director, foreign ownership have significant effects on CSR disclosure index. On the other hand, banks’ profitability, bank size and institutional ownership have insignificant relationship with corporate social responsibility disclosure index (CSRD). This study will play a significant role to find out the determinants of CSR disclosures and help the authority to give more attention on CSR reporting after post pandemic phase to tackle down the pandemic challenges and crises.